Inferência da conectividade neuronal via estimação de medidas da teoria da informação - Girardi, Victor Augusto (Universidade Federal de São Carlos, 2021)
Information theory studies how communication systems integrate, encode, compute, and transmit information. The neural system is an example where communication takes place with neurons responding to stimuli and conducting electrical impulses by means of action potentials thereby causing a flow of neuronal information throughout the system. In this sense, one of the goals of this work is to study some information theory measures, with special attention to their application in the study of neural connectivity. The second goal is to understand the process of mathematical modeling of neuronal spike-trains prescribed from stochastic chains with memory of variable length as well as proposing estimators for the information metrics based on samples of these chains. Lastly, we study the performance of the estimators via computational simulation.
Neural connectivity inference from the estimation of information theory measures
Keywords: Cadeias estocásticas de memória com alcance variável; Teoria da informação; Inferência em processos estocásticos; Neurociência; Chains with memory of variable length; Information theory; Statistical inference in stochastic processes; Neuroscience; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE DE DADOS; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::INFERENCIA EM PROCESSOS ESTOCASTICOS; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::PROBABILIDADE E ESTATISTICA APLICADAS